Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the quadratic equation [tex]\( y^2 - 9y + 14 = 0 \)[/tex], we can use the quadratic formula, which is given by:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
In this quadratic equation, [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are the coefficients of [tex]\(y^2\)[/tex], [tex]\(y\)[/tex], and the constant term, respectively. Here, [tex]\(a = 1\)[/tex], [tex]\(b = -9\)[/tex], and [tex]\(c = 14\)[/tex].
First, we need to calculate the discriminant, which is [tex]\( b^2 - 4ac \)[/tex].
1. Calculate the discriminant:
[tex]\[ \Delta = (-9)^2 - 4 \cdot 1 \cdot 14 \][/tex]
[tex]\[ \Delta = 81 - 56 \][/tex]
[tex]\[ \Delta = 25 \][/tex]
Since the discriminant is positive, we have two real solutions. Now, we use the quadratic formula to find these solutions.
2. Calculate the solutions:
[tex]\[ y_1 = \frac{-(-9) + \sqrt{25}}{2 \cdot 1} \][/tex]
[tex]\[ y_1 = \frac{9 + 5}{2} \][/tex]
[tex]\[ y_1 = \frac{14}{2} \][/tex]
[tex]\[ y_1 = 7 \][/tex]
[tex]\[ y_2 = \frac{-(-9) - \sqrt{25}}{2 \cdot 1} \][/tex]
[tex]\[ y_2 = \frac{9 - 5}{2} \][/tex]
[tex]\[ y_2 = \frac{4}{2} \][/tex]
[tex]\[ y_2 = 2 \][/tex]
Thus, the solutions to the equation [tex]\( y^2 - 9y + 14 = 0 \)[/tex] are:
[tex]\[ y = 7, 2 \][/tex]
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
In this quadratic equation, [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are the coefficients of [tex]\(y^2\)[/tex], [tex]\(y\)[/tex], and the constant term, respectively. Here, [tex]\(a = 1\)[/tex], [tex]\(b = -9\)[/tex], and [tex]\(c = 14\)[/tex].
First, we need to calculate the discriminant, which is [tex]\( b^2 - 4ac \)[/tex].
1. Calculate the discriminant:
[tex]\[ \Delta = (-9)^2 - 4 \cdot 1 \cdot 14 \][/tex]
[tex]\[ \Delta = 81 - 56 \][/tex]
[tex]\[ \Delta = 25 \][/tex]
Since the discriminant is positive, we have two real solutions. Now, we use the quadratic formula to find these solutions.
2. Calculate the solutions:
[tex]\[ y_1 = \frac{-(-9) + \sqrt{25}}{2 \cdot 1} \][/tex]
[tex]\[ y_1 = \frac{9 + 5}{2} \][/tex]
[tex]\[ y_1 = \frac{14}{2} \][/tex]
[tex]\[ y_1 = 7 \][/tex]
[tex]\[ y_2 = \frac{-(-9) - \sqrt{25}}{2 \cdot 1} \][/tex]
[tex]\[ y_2 = \frac{9 - 5}{2} \][/tex]
[tex]\[ y_2 = \frac{4}{2} \][/tex]
[tex]\[ y_2 = 2 \][/tex]
Thus, the solutions to the equation [tex]\( y^2 - 9y + 14 = 0 \)[/tex] are:
[tex]\[ y = 7, 2 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.